Pengaruh Perceived Organizational Support terhadap Self Efficacy, Work Engagement dan Career Satisfaction pada Pegawai Rumah Sakit di Jakarta - Budhy Vipyana; Tantri Yanuar Rahmat Syah (JUDICIOUS, 2023)
Every employee certainly wants a good career. This can be started by choosing the place of work and position offered. When career goals are not achieved, employees will experience dissatisfaction in their work careers and will certainly negatively impact the company. Knowing this, career satisfaction is important in influencing employee behavior that can benefit companies. Career satisfaction is certainly influenced by many things, such as perceived organizational support for self-efficacy and work engagement. Based on this, this study aims to see the influence of perceived organizational support on self-efficacy, work engagement and career satisfaction. The sample of this study was 135 employees in Jakarta area hospitals. This type of research is deductive, and data collection by spreading questionnaires. The analysis method used is Structural Equation Model (SEM). The study's results concluded: First, perceived organizational support positively affects career satisfaction. Second, self-efficacy is positively impacted by perceived organizational support. Third, professional happiness is positively impacted by self-efficacy. Fourth, job engagement benefits from self-efficacy. Fifth, perceived organizational support has a positive effect on work engagement. Sixth, work engagement has a positive effect on career satisfaction.